HIV‐specific antibody‐dependent phagocytosis matures during HIV infection. Issue 8 (10th June 2014) - Ana‐Sosa‐Batiz, Fernanda; Johnston, Angus P R; Liu, Haiyin; Center, Robert J; Rerks‐Ngarm, Supachai; Pitisuttithum, Punnee; Nitayaphan, Sorachai; Kaewkungwal, Jaranit; Kim, Jerome H; Michael, Nelson L; Kelleher, Anthony D; Stratov, Ivan; et al.
Abstract : Antibody‐dependent phagocytosis (ADP) is a potentially important immune mechanism to clear HIV. How HIV‐specific ADP responses mature during HIV infection or in response to vaccinations administered, including the partially successful RV144 HIV vaccine, is not known. We established a modified ADP assay to measure internalisation of HIV antibody (Ab)‐opsonised targets using a specific hybridisation internalisation probe. Labelled beads were coated with both biotinylated HIV gp140 envelope protein and a fluorescent internalisation probe, opsonised with Abs and incubated with a monocytic cell line. The fluorescence derived from the fluorescent internalisation probe on surface‐bound beads, but not from internalised beads, was quenched by the addition of a complementary quencher probe. HIV Env‐specific ADP was measured in 31 subjects during primary infection and early chronic HIV infection. Although ADP responses were present early during HIV infection, a significant increase in ADP responses in all 31 subjects studied was detected ( P <0.001). However, when we tested 30 HIV‐negative human subjects immunised with the Canarypox/gp120 vaccine regimen (subjects from the RV144 trial) we did not detect HIV‐specific ADP activity. In conclusion, a modified assay was developed to measure HIV‐specific ADP. Enhanced ADP responses early in the course of HIV infection were observed but no ADP activity was detected following the vaccinations administered in the RV144 trial. Improved vaccine regimens may be needed to capitalise on ADP‐mediated immunity against HIV.